Pharmacokinetics of Single-Dose Oral Pregabalin Administration in Normal Cats - Esteban, Michaela A.; Dewey, Curtis W.; Schwark, Wayne S.; Rishniw, Mark; Boothe, Dawn M. (Frontiers in Veterinary Science, 2018)
Objective: To describe the pharmacokinetic parameters of oral pregabalin in normal cats after single oral dosing. Animals: Six healthy adult research cats. Procedures: Following sedation and indwelling catheter placement, one oral (4 mg/kg) dose of pregabalin was administered. Blood samples were collected at 0, 15 and 30 minutes and 1, 1.5, 2, 3, 4, 6, 8, 12, 24 and 36 hours after administration. Plasma pregabalin concentrations were measured by high-performance liquid chromatography and subjected to pharmacokinetic analysis using commercial software. Results: Four of six cats developed moderate sedation after pregabalin administration. The peak pregabalin concentration was 8.3 ± 1.6 g/ml which occurred at 2.9 ± 1.2 hours. Elimination half-life was 10.4 ± 2.6 hours and area under the curve was 133.9 ± 71.5 g-h/ml. Time above the minimum therapeutic concentration for seizure control in dogs and people (2.8 g/ml) was 17.6 ± 6.2 hours. Using these data, predicted minimum, maximum and average steady state concentrations were calculated for 12 and 24 hour dosing intervals. Conclusions and Clinical Relevance: Pregabalin (4 mg/kg) administered orally to cats results in plasma concentrations within the range considered to be efficacious for seizure control in dogs and humans between 1.5 and at least 12 hours. Because of moderate sedative side effects in the majority of cats at this dose and high calculated maximum steady state concentrations, a lower dose, given more frequently (2 mg/kg, q 12 hrs), should be evaluated in prospective clinical studies.